Dukungan Sosial Penghargaan Teman Sebaya Dalam Mengatasi Fenomena Quarter Life Crisis Di Panti Sosial Bina Remaja Taruna Jaya 1 - Azrial Rizki Nurdiansyah; Ati Kusmawati (Observasi : Jurnal Publikasi Ilmu Psikologi, 2024)
The phenomenon of quarter life crisis is a phase where teenagers feel a number of conditions, namely conditions of worry, confusion, fear, anxiety, to despair that appear in adolescents in navigating life and reaching for their future. There are 6 indicators in the quarter life crisis limitation area for adolescents, including hopes and dreams in which they have fear of their goals not being achieved, challenges in the academic aspect are a form of concern about the education they are currently achieving, religion and spirituality related to the lack of worship momentum which are still not consistent, Career talks about the anxiety of getting a decent job, Friendship, romance and family relations are fears about forms of community acceptance in the future and whether you can get married and support your family well in the future, as well as Self-identity which is concerned with finding identity and experienced identity crisis. This research used a descriptive qualitative method which was carried out at the Taruna Jaya 1 Youth Development Institution, East Jakarta. Informants in this study amounted to 9 people consisting of 1 companion with consideration of this companion who knows more about the character, behavior of the orphans, and sufficient emotional closeness. 6 orphans with the consideration that these six orphans feel the QLC phenomenon in 6 QLC indicators, and 2 peers with WBS status also with the consideration that the two orphans often provide social support to their peers in the orphanage during the coaching process. Fellow wbs here have an effort to overcome this QLC through a rewarding social support approach. Social support that is often carried out is in the form of positive evaluation, having a positive impact on others, giving positive influence, and positive views on others so that effective social functioning is created in the future.